Phenomenology of future-oriented mind-wandering episodes - Stawarczyk, David; Cassol, Helena; D'Argembeau, Arnaud (Frontiers in Psychology, 2013)
Recent research suggests that prospective and non-prospective forms of mind-wandering possess distinct properties, yet little is known about what exactly differentiate between future-oriented and non-future-oriented mind-wandering episodes. In the present study, we used multilevel exploratory factor analyses to examine the factorial structure of various phenomenological dimensions of mind-wandering, and we then investigated whether future-oriented mind-wandering episodes differ from other classes of mind-wandering along the identified factors. We found that the phenomenological dimensions of mind-wandering are structured in four factors: representational format (inner speech vs. visual imagery), personal relevance, realism/concreteness, and structuration. Prospective mind-wandering differed from non-prospective mind-wandering along each of these factors. Specifically, future-oriented mind-wandering episodes involved inner speech to a greater extent, were more personally relevant, more realistic/concrete, and more often part of structured sequences of thoughts. These results show that future-oriented mind-wandering possesses a unique phenomenological signature and provide new insights into how this particular form of mind-wandering may adaptively contribute to autobiographical planning.